THE EFFECT OF REPLACING CONCENTRATE WTH MAGGOTS (Hermetia illucens) ON THE QUALITY OF ISA BROWN CHICKEN EGGS STORED FOR FOUR WEEKS - M. M., Zahro,; Astawa, I P. A.; Suasta, I M. (Jurnal Peternakan Tropika, 2024)
This research aims to determine the effect of replacing concentrate with maggot on the storage time of purebred chicken eggs to obtain better quality. This research was carried out in Candikusuma Village, Melaya District, Jembrana Regency, Bali and lasted for 8 weeks. The design used was a Completely Randomized Design (CRD) with four treatments and four replications, so there were 16 experimental units. Each experimental unit used 4 laying hens. The four treatments were chickens given food without maggots (P0), Chickens given 3% maggots as a substitute for concentrate (P1), Chickens given 4% maggots as a substitute for concentrate (P2), Chickens given 5% maggots as a substitute for concentrate. (P3). Observations on egg quality were carried out for four weeks by taking 4 eggs using 4 treatments and 4 repetitions so that a total of 16 eggs were broken each week. The variables observed included egg specific gravity, HU ( haugh unit ), egg weight, egg yolk index, egg white index and egg pH. The research results showed that there was no difference in HU (Haugh Unit), egg weight, egg yolk index, egg white index, and pH at P0. Meanwhile, laying hens that were treated with P1, P2 and P3 showed significantly different results regarding egg density. Based on the results of this research, it can be concluded that replacing concentrate with maggot in feed gives the same results on the quality of purebred chicken eggs.